Laboratory Parameters are Possible Prognostic Markers in Patients with Advanced-stage NSCLC Treated with Bevacizumab plus Chemotherapy - Svaton, Martin; Blazek, Jiri; Krakorova, Gabriela; Buresova, Marcela; Teufelova, Zuzana; Vodicka, Josef; Hurdalkova, Karolina; Barinova, Magda; Pesek, Milos (Journal of Cancer, 2021)
Purpose: To investigate potential associations between selected laboratory markers (CRP, LDH, albumin, sodium, hemoglobin, neutrophils, and neutrophils/lymphocytes ratio [NLR]) and outcomes in patients with non-small cell lung cancer (NSCLC) treated with bevacizumab (BEV) plus chemotherapy. Patients and Methods: We retrospectively analyzed 105 patients with NSCLC from the Czech TULUNG registry treated at University Hospital in Pilsen with BEV + chemotherapy. Response to therapy was tested by Fisher's exact test. Survival statistics were evaluated using the Kaplan-Meier method and Cox analysis. Results: We showed significantly better disease control rate when CRP, albumin, hemoglobin, and NLR were within established "normal" values. In univariate analysis, normal values of CRP, LDH, albumin, sodium, hemoglobin, neutrophils, and NLR were associated with better overall survival (OS). Normal values of CRP, albumin, hemoglobin, neutrophils, and NLR were associated also with better progression-free survival (PFS). In a multivariate Cox model, normal values of LDH, albumin, and NLR were associated with significantly better OS while normal CRP, albumin, and NLR were associated with better PFS. Conclusions: LDH and sodium appear to be possible prognostic markers for BEV treatment in combination with chemotherapy in NSCLC. The parameters associated with inflammatory response (CRP, NLR, albumin, and possibly hemoglobin) appear to be promising predictive markers for this treatment combination.
Keywords: inflammation; predictive; prognostic; albumin; CRP; bevacizumab; NSCLC